Funcionarios Bienestar Estudiantil. (UNED, 2025)
En el orden usual: Joaquín Jiménez, Adelita Sibaja, Nidia Lobo, Sandra Chávez, Iris Amalia Ramírez. Sentados: Rocío Céspedes, Jonatan Morales, Marvin Chavarría, Blanca Rosa Aguilar y Fanny Larios